RETRACTED: State asset management paradigm in the quasi-public sector and environmental sustainability: Insights from the Republic of Kazakhstan - Zhanbayev, Rinat A.; Yerkin, Albina Y.; Shutaleva, Anna V.; Irfan, Muhammad; Gabelashvili, Kakhaberi; Temirbaeva, G. R.; Chazova, Irina Yu.; Abdykadyrkyzy, Rimma (Frontiers in Environmental Science, 2023)
This study aims to improve state regulation and administration of quasi-state sector of environmental sustainability in the Republic of Kazakhstan within the social sustainability paradigm. This study is due to the need to search the balance of business interests, and efficient use of resources and their conservation on a global scale. The issues of state asset management are identified and ways to resolve them are proposed based on the corporate foresight methodology using the strategic planning mechanism. As a result of the analysis of the tools introduced into the practice of leading transnational corporations, the main directions are identified in which it is advisable to take measures aimed at streamlining and optimizing the quasi-public sector in the Republic of Kazakhstan. This article presents proposals for improving state regulation and administration of quasi-public companies in the Republic of Kazakhstan. The outcomes of this study can assist policymakers, experts, and stakeholders in gaining awareness about these problems while simultaneously improving sustainability practices.